Effect of Combined Foot Bath and Foot Massage Therapy on Blood Pressure in Hypertensive Patients at Tambakrejo Health Center, Surabaya - Naharil Mumtazah; Minarti; Sari Lutfiyah; Mohammad Najib (International Journal of Advanced Health Science and Technology, 2026)
Hypertension, often referred to as a "silent killer," is a prevalent non-communicable disease that significantly contributes to cardiovascular events and other serious health complications. Despite various pharmacological treatments, many hypertensive patients seek non-pharmacological alternatives to manage their condition. This study investigates the effect of combined foot bath and foot massage therapy on blood pressure reduction in hypertensive patients. A quasi-experimental pretest-posttest control group design was employed, with 40 participants selected through purposive sampling. These participants were assigned to either the intervention group, which received the combined therapy for three consecutive days, or the control group, which did not receive the intervention. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. The data were analyzed using paired sample t-tests and independent sample t-tests. The results showed a significant decrease in both systolic and diastolic blood pressure in the intervention group, with p-values of 0.000 and 0.025, respectively. In contrast, no significant change was observed in the control group (p > 0.05). The findings suggest that the combination of foot bath and foot massage therapy is effective in lowering blood pressure in hypertensive patients. This non-pharmacological approach offers a promising complementary treatment for hypertension management, particularly for patients who are seeking alternatives to medication. Further research with a larger sample size and longer intervention period is recommended to confirm these results and explore the long-term effects of this therapy.